The plastid metalloprotease FtsH6 and small heat shock protein HSP21 jointly regulate thermomemory in Arabidopsis - Mastoureh Sedaghatmehr (Nature Portfolio, 2016)
Exposure of plants to heat can promote increased tolerance to subsequent heat stress. Here, the authors show that prolonged expression of Arabidopsissmall heat shock protein HSP21 promotes this thermomemory effect and that HSP21 levels are regulated by the plastid metalloprotease FtsH6 during the memory period.